Smoking control: challenges and achievements - da Silva, Luiz Carlos Corrêa (J Bras Pneumol, 2016)
Smoking is the most preventable and controllable health risk. Therefore, all health care professionals should give their utmost attention to and be more focused on the problem of smoking. Tobacco is a highly profitable product, because of its large-scale production and great number of consumers. Smoking control policies and treatment resources for smoking cessation have advanced in recent years, showing highly satisfactory results, particularly in Brazil. However, there is yet a long way to go before smoking can be considered a controlled disease from a public health standpoint. We can already perceive that the behavior of our society regarding smoking is changing, albeit slowly. Therefore, pulmonologists have a very promising area in which to work with their patients and the general population. We must act with greater impetus in support of health care policies and social living standards that directly contribute to improving health and quality of life. In this respect, pulmonologists can play a greater role as they get more involved in treating smokers, strengthening anti-smoking laws, and demanding health care policies related to lung diseases.